Resonances of greek-latin classics in the works of Fyodor Dostoevsky: a critical analysis - Yasin, Ghulam; Ali, Shaukat; Shahzad, Kashif (Acta Scientiarum. Language and Culture, 2021)
This research aims to probe the classical elements in the works of Fyodor Dostoevsky and to show the author’s bent towards the classical authors and traditions. Dostoevsky is the giant literary figure of 19th-century Russian literature and he belongs not only to a particular time but to all times like many other great classic writers. The research is significant for exposing the author’s affiliation towards the epic poetry of Homer and Hesiod and the dramas of the preeminent Athenian tragedians, Aeschylus, Sophocles, and Euripides. Dostoevsky also becomes classic based on his dealings with the themes dealt by the classics like love, fight for honour, real-life presentation, the conflict between vice and virtue and the struggle of his tragic heroes to reach their goal. The research proves that Dostoevsky is a classic among the classics because of having close resonance with the classics in the art of characterization, the portrayal of tragic heroes, theme building and by including some elements of tragedy. The qualitative research is designed on the descriptive-analytic method by using the approach of Classicism presented by Mark Twain.